FRAUD DETECTION AT PT NESINAK INDUSTRIES IS SEEN FROM TIME PRESSURE AND WORK EXPERIENCE - Patminingsih; Yusuf Faisal; Egi Gumala Sari (CV. Radja Publika, 2023)
This study aims to obtain empirical evidence on the effect of work experience, time pressure on fraud detection. For this study using quantitative type of research. This research was conducted using questionnaires distributed to employees working at PT Nesinak, as many as 116 people filled out questionnaires that were distributed directly. To get the results of this study, researchers used PLS SEM version 3.0. The results of this study found that work experience had a positive and statistically significant effect on fraud detection, but time pressure had a negative but statistically not significant effect on fraud detection. This research focuses on fraud detection at PT Nesinak that involves all parts.